The impact of markups and wages on changes in the level of inflation in Poland - Kosztowniak, Aneta (Managerial Economics, 2024)
This paper analysis of the impact of markups and wages of enterprises on changes in the level of inflation in Poland in the years 2007-2022. the impact of markups and wages on changes in CPI were assessed using the VECM model, the impulse responses, and the variance decomposition. The results indicate that industrial sector, including the mining and quarrying section, showed the highest dynamics of changes in markups and wages. In the years 2005–2022, the impact of markups on changes in CPI was stronger, although it was losing importance, with a weaker but growing impact of wages. Forecasts of the degree of clarification of the CPI in Poland indicate a greater importance of markups, with the impact of wages weaker by half, but growing over time. The paper extends the state of theoretical and empirical studies on the determinants of the CPI and the inflation expectations. It also considers the context of persistent exogenous and endogenous shocks from the COVID-19 pandemic and the war in Ukraine, and changes in demand and supply impulses. The results of this study may be valuable as a contribution to the literature on inflation and its forecasts, and for monetary policy makers.